2017
DOI: 10.1038/srep45329
|View full text |Cite
|
Sign up to set email alerts
|

Exosome-associated AAV2 vector mediates robust gene delivery into the murine retina upon intravitreal injection

Abstract: Widespread gene transfer to the retina is challenging as it requires vector systems to overcome physical and biochemical barriers to enter and diffuse throughout retinal tissue. We investigated whether exosome-associated adeno-associated virus, (exo-AAV) enabled broad retinal targeting following intravitreal (IVT) injection, as exosomes have been shown to traverse biological barriers and mediate widespread distribution upon systemic injection. We packaged an AAV genome encoding green fluorescent protein (GFP) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
106
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 116 publications
(111 citation statements)
references
References 45 publications
5
106
0
Order By: Relevance
“…13 The natural release of a fraction of recombinant AAV vectors associated with exosomes (exosome-associated AAVs [exo-AAVs]) in the cell medium during vector production has been recently described. 14 The use of exo-AAV vectors has been demonstrated to enhance transduction in the setting of gene transfer to the retina, 15 the nervous system, 16 and the inner ear. 17 In the present study, we tested the ability of exo-AAV vectors to transduce the liver and drive efficient correction of hemophilia B.…”
Section: Introductionmentioning
confidence: 99%
“…13 The natural release of a fraction of recombinant AAV vectors associated with exosomes (exosome-associated AAVs [exo-AAVs]) in the cell medium during vector production has been recently described. 14 The use of exo-AAV vectors has been demonstrated to enhance transduction in the setting of gene transfer to the retina, 15 the nervous system, 16 and the inner ear. 17 In the present study, we tested the ability of exo-AAV vectors to transduce the liver and drive efficient correction of hemophilia B.…”
Section: Introductionmentioning
confidence: 99%
“…One possible explanation is that secreted viral particles may be inherently different than those found intracellularly. Several recent papers have identified secreted rAAV particles inside vesicular bodies such as exosomes [40][41][42][43][44][45][46][47]. The secreted rAAVs utilized in our study may be associated with exosomes and this association could potentially alter the way in which they interact with the target cell.…”
Section: Discussionmentioning
confidence: 90%
“…We utilized exo-AAV in this study has we have previously shown that this vector system has attributes such as enhanced transduction to CNS 21 , liver 32 , inner ear 33 , and retina 34 compared to conventional AAV. Exo-AAV also has a benefit of antibody evasion which may have clinical relevance in patients with pre-existing humoral immunity to AAV 20, 32 .…”
Section: Discussionmentioning
confidence: 99%